Effect of Capital Structure, Audit Quality and Company Profitability on Accounting Conservatism - Iswanaji, Chaidir; Nugraheni, Agustina Prativi (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2023)
This study aims to examine several factors that are thought to affect accounting conservatism, namely Capital Structure, Audit Quality, and Company Profitability. This study uses quantitative methods. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange. The sample selection technique is based on purposive sampling. The analytical method used in this study is panel regression, which is a combination of cross-sectional data and time-series data. The results showed that the capital structure variable had no effect on accounting conservatism with a value of 0.1136 > 0.05, then the audit quality variable had a significant effect on accounting conservatism with a value of 0.0014 < 0.05, and the company's profitability variable has no effect on accounting conservatism with a value of 0.9068 > 0.05. Based on the results of the Simultaneous Test that the independent variables namely Capital Structure, Audit Quality, and Company Profitability together have a significant effect on accounting conservatism with a Prob value (F-statistic) of 0.007847 <0.05